BIBLICAL INTERPRETATION WITHIN THE CONTEXT OF ESTABLISHED BIBLE STUDY GROUPS - Conradie, Ernst M. (Scriptura, 2001)
1. Introduction There exists an abundant corpus of popular literature in South Africa for Bible study groups. There are also a number of publications on appropriate Bible study methods for groups. These texts often include sections on group dynamics and interaction, drawing on the equally extensive corpus of literature in psychology and sociology on the functioning of groups. In the field of theological hermeneutics the importance of interpretative communities and of "reading the Bible in communion" has often been stressed.l There is no need here to repeat or to summarise the consensus emerging from such literature. There is a need though, to relate the group dynamics within Bible Study groups to the theory of Biblical interpretation. This contribution will therefore offer a few brief hermeneutical observations on the interpretation of the Bible in a group context.